PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA GURU DI SMAS NURUL ISLAM INDONESIA MEDAN - Rahma Aulia Ashari; Khairuddin Lubis; Abdul Halim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Organizational Citizenship Behavior can increase the stability of organizational performance. Conscientious employees tend to maintain consistently high-performance levels, thereby reducing variability in work unit performance. However, improving human performance is one of the toughest challenges in the world, namely changing the way other people think. Leaders can change the way they think or perform if they can change the way other people think. In this case, OCB is needed to improve employee performance. The title that the researcher adopted in this research is "The Influence of Organizational Citizenship Behavior on Teacher Performance at SMAS Nurul Islam Indonesia Medan" so the research approach used is quantitative research. The findings were that in the f test, the calculated F value was 11.915 > F table value 4.54 with a significance value of 0.004 < 0.05. In the t-test, the calculated T value was 3.452 > T table value 1.75305 with a significance value of 0.004 < 0.05. Then in the regression coefficient, the Unstandardized Coefficients value B for Organizational Citizenship Behavior shows a positive value, namely 0.721. These results indicate that Organizational Citizenship Behavior has a positive and significant effect on teacher performance. Ho is rejected and Ha is accepted. Based on the results of this data analysis, it can be stated that "there is a positive and significant influence on Organizational Citizenship Behavior on Teacher Performance at SMAS Nurul Islam Indonesia Medan". Based on the coefficient of determination (R Square) of 0.443, the magnitude of the influence of Organizational Citizenship Behavior on teacher performance at SMAS Nurul Islam Indonesia Medan is 44.3%.